2014
DOI: 10.14419/ijm.v2i2.3406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chlorine dioxide on Enterococcus faecalis in exponential, stationary and starvation phases in extracted human teeth - an invitro study

Abstract: Background: Enterococcus Faecalis (E faecalis) is isolated usually from failed root canal treated teeth. It can bind to dentin and co-aggregate with other organisms. The organism is resistant to the intracanal medicaments and irrigants. It has the ability to produce biofilms and survive within the root canal. They may develop resistance at different phases of bacterial growth cycle. Objective: To study the effect of chlorine dioxide on different phases of E faecalis growth cycle for 1 and 3 min duration. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Lundstrom, et al, [41] noted that ClO2 0.4%, exhibited little bactericidal activity against P. nigrescens, and was significantly less effective than NaOCl. In the other hand, Eddy, et al, [42] showed that NaOCl was more effective for bacterial inhibition than chlorine dioxide 13.8%, highlighting that chlorine dioxide can also eradicate E. faecalis in 30 min and in a higher concentration could eliminate it completely, later Ozkan, et al, [43] indicated that 10% and 13.8% chlorine dioxide and 5.25% NaOCl were effective in eliminating E. faecalis in 30 min, Somayaji, et al, [44] and Ersoy, et al, [45] also showed that NaOCl and ClO2 caused almost the same bacterial inhibition (70%). Al-bayaty, et al, [46] found that ClO2 gel had an effective antibacterial action against dental biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Lundstrom, et al, [41] noted that ClO2 0.4%, exhibited little bactericidal activity against P. nigrescens, and was significantly less effective than NaOCl. In the other hand, Eddy, et al, [42] showed that NaOCl was more effective for bacterial inhibition than chlorine dioxide 13.8%, highlighting that chlorine dioxide can also eradicate E. faecalis in 30 min and in a higher concentration could eliminate it completely, later Ozkan, et al, [43] indicated that 10% and 13.8% chlorine dioxide and 5.25% NaOCl were effective in eliminating E. faecalis in 30 min, Somayaji, et al, [44] and Ersoy, et al, [45] also showed that NaOCl and ClO2 caused almost the same bacterial inhibition (70%). Al-bayaty, et al, [46] found that ClO2 gel had an effective antibacterial action against dental biofilm.…”
Section: Discussionmentioning
confidence: 99%